2015
DOI: 10.1080/10538720.2015.1022272
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Being Out on a Queer Person's Self-Compassion

Abstract: Recent changes in societal attitudes toward lesbian, gay, and bisexual identities have resulted in more people openly identifying with sexual minority status. Due to research on the effects of denying one's sexual orientation and the negative effects of this, many have advocated for more openness in queer sexual orientation. Compassion means connecting to the suffering of others not by avoiding their pain but instead by identifying it so that the feeling of kindness may emerge. Self-compassion, therefore, invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
(61 reference statements)
4
15
0
Order By: Relevance
“…LGB individuals who experienced parental warmth and safeness reported higher subjective happiness as adults (Greene & Britton, 2015). Self-disclosing personal sexual and relational orientation is an important precursor to receiving social support from family and friends, with those who are more comfortable self-disclosing demonstrating an increased sense of belonging and decreased sense of isolation (Crews & Crawford, 2015). Conversely, familial rejection and decreased social support has been linked to negative mental health outcomes in LGB individuals, including higher rates of depression and suicidal ideation, substance abuse, risky sexual behavior, and negative feelings about being LGB (Ryan, Huebner, Diaz, & Sanchez, 2009; Wright & Perry, 2006).…”
Section: Social Support and Subjective Well-beingmentioning
confidence: 99%
“…LGB individuals who experienced parental warmth and safeness reported higher subjective happiness as adults (Greene & Britton, 2015). Self-disclosing personal sexual and relational orientation is an important precursor to receiving social support from family and friends, with those who are more comfortable self-disclosing demonstrating an increased sense of belonging and decreased sense of isolation (Crews & Crawford, 2015). Conversely, familial rejection and decreased social support has been linked to negative mental health outcomes in LGB individuals, including higher rates of depression and suicidal ideation, substance abuse, risky sexual behavior, and negative feelings about being LGB (Ryan, Huebner, Diaz, & Sanchez, 2009; Wright & Perry, 2006).…”
Section: Social Support and Subjective Well-beingmentioning
confidence: 99%
“…Nevertheless, research on self-compassion in gay men is still scant. For example, one study found that gay men who have come out had a higher sense of self-compassion (Crews & Crawford, 2015). Another study found that self-compassion is a predictor of greater life satisfaction in a sample of gay men (Jennings & Tan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…individuals' coming-out, which allows them to receive social support (Crews & Crawford, 2015). Our findings indicating a difference in the sequence of the mediators between the bisexual and LG groups show that not only does the level of perceived social support predict sexual minority individuals' healthy coping strategies, such as self-compassion, but selfcompassion can predict the social support that these individuals receive from their surroundings.…”
Section: Path Sie (β) Se 95% CImentioning
confidence: 66%
“…Self-compassion is an essential construct for LGB individuals, particularly with respect to identity development, because it encourages LGB individuals to be aware of their failures, inadequacies, rejections, and experiences of difficulties during their sexual identity development. To date, a few researchers (e.g., Crews & Crawford, 2015;Liao et al, 2015) have investigated self-compassion experienced by LGB individuals, demonstrating that a higher level of selfcompassion was positively associated with positive identity in their experiences of coming out.…”
Section: Self-compassion and Social Supportmentioning
confidence: 99%